Computational characterization of isomeric C4H2O systems: Thermochemistry, vibrational frequencies, and optical spectra for butatrienone, ethynyl ketene, butadiynol, and triafulvenone. Issue 6 (29th December 2015) - Şahin, Sevgi; Bleda, Erdi A.; Altun, Zikri; Trindle, Carl
Abstract : Species of empirical formula C4 H2 O have been invoked either as elusive intermediates in flames or oxidations on heterogeneous catalysts, or as long‐lived species in the interstellar medium. Butatrienone has been characterized experimentally, but isomers ethynyl ketene, butadiynol, and trifulvenone have been described only by computational modeling. Triafulvenone is of special interest as the ketene analog of the carbonyl compound cyclopropenone; both species contain seriously strained three‐membered rings. In contrast to cyclopropenone, which is detected in the interstellar medium, triafulvenone continues to elude experimental capture. The contrast is attributed to a degree of aromatic stabilization in cyclopropenone and anti‐aromatic destabilization in triafulvenone. In this report, we characterize the structure, vibrational and electronic spectra, and thermochemistry for triafulvenone and three of its isomers, butatrienone, ethynyl ketene, and butadiynol to assist experimental detection of these elusive species. Our calculations have shown that triafulvenone is the least stable of these four isomers; even the well‐known butatrienone, is not the most stable. The so far undetected ethynyl ketene is thermodynamically the most stable of these isomers. To facilitate experimental detection of these species we provide vibrational frequencies calculated using both B3LYP/cc‐pVTZ and MP2/cc‐pVTZ level model chemistry corrected for anharmonicity including the possibility that the spectra may include overtones and combination bands for these species The regions of intense IR absorption and most important frequencies are also underlined for all the species involved. To guide the search for short‐lived C4 H2 O species, we also characterize the optical spectrum. © 2015 Wiley Periodicals, Inc. Abstract : Infrared absorption spectra may allow discrimination among the elusive C4 H2 O isomers. Absorption above 3500 cm −1 indicates the butadiynol; assuming that there is absorption in the range 2100 to 2400 cm −1, then the decision rests on the presence or absence of absorptions near 1500 or 1700 cm −1 .